The relationships among knowledge management processes, innovation, and organisational performance in the Iraqi MTS - Al-Hakim, Laith Ali Yousif; Hassan, Shahizan (2012)
Present study examines of the relationships among knowledge management processes, innovation, and organisational performance in the Iraqi mobile telecommunications sector.The perspective of this research suggests that knowledge processes are essential capabilities for effective innovation and organisational performance. Through analysis of surveys collected from 220 mid-level managers, present study empirically tested a proposed theoretical framework by estimating structural equation model. The results show that knowledge management processes had a statistically significant and direct positive effect on innovation.Additionally, the direct relationship of knowledge management processes with organisational performance was positively affected, but it was not statistically significant.More importantly, the findings indicate that knowledge management processes had a positive and statistically significant effect on organisational performance through the partial mediation effect of innovation. Present study concludes with a conclusions and contribution of the research.